2012
DOI: 10.1111/j.1447-0594.2012.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Delusions of Korean patients with Alzheimer's disease: Study of drug‐naïve patients

Abstract: This study showed that delusions are associated with global cognitive dysfunction. Although paranoid delusions are the most common, misidentification and mixed delusions comprised significant portions of delusions in AD patients, and appeared in the later stages of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In particular, home misidentification appears to be underestimated in previous studies, 10,12,16,19 whereas the Capgras syndrome (which seems far more frequent in DLB than in AD) was detected in similar percentages and consistently with our result. [10][11][12]16,17,20 Interestingly, even if Capgras syndrome is commonly referred to misidentification of people, our study found that Capgras for objects/animals is not so rare.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In particular, home misidentification appears to be underestimated in previous studies, 10,12,16,19 whereas the Capgras syndrome (which seems far more frequent in DLB than in AD) was detected in similar percentages and consistently with our result. [10][11][12]16,17,20 Interestingly, even if Capgras syndrome is commonly referred to misidentification of people, our study found that Capgras for objects/animals is not so rare.…”
Section: Discussionmentioning
confidence: 52%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Even in DLB, where they are observed more frequently, the percentage varies considerably from 38% to 78.3%. 16 The variability of previous reports is probably accounted for by different types of included dementia, different severity of cognitive impairment, and above all different assessment definitions/methods for MD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that delusion is closely related with agitation and aberrant motor behavior,12,13 and these physical symptoms apparently lead to problems in assessing these time-consuming tests. Moreover, patients with delusions frequently have persecutory delusion,14,15 and as a results some patients with this delusion may resist diagnostic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Persecutory delusions occur early during the progression of AD and associate with disruption of frontostriatal circuits [107]. One study found delusions in 27.4% of AD patients, with paranoid delusions being the most common (60.3%), followed by misidentification delusions (19.0%), and then mixed delusions (17.5%), the latter appearing later and associated with greater cognitive impairment [108]. Psychotic patients show greater A β 1-42 at autopsy [109].…”
Section: Psychosismentioning
confidence: 99%